Pemberdayaan Kampung Ayapo menuju Kebangkitan Kampung Adat - Simon Abdi K. Frank; Septinus Saa; Marlina Flassy; Hiskia C.M. Sapioper; Usman Idris (Universitas Cenderawasih, 2022)
This research aims to examine the forms of empowerment, obstacles faced and empowerment strategies in the Ayapo traditional village, which are dissected internally and externally. The research method is descriptive qualitative. The research methods used are observation and interviews. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The research findings show that the village development program is implemented by empowering the community to increase community participation in development, the priorities of the development program are determined by deliberating on development plans that are adapted to internal conditions and external situations. The obstacle identified was the limited budget and program implementation. The strategy developed is to establish communication among stakeholders to partner in the implementation of empowerment programs.